APPLICATION OF PUZZLE MEDIA TOWARDS THE BEGINNING READING AND WRITING SKILLS OF CLASS II STUDENTS IN PRIMARY SCHOOL NEGERI 27 BANDA ACEH - Mauliza, Deli; Sulaiman, Sulaiman; Yamin, M. (Universitas Syiah Kuala, 2024)
Puzzle media is an educational game tool for children by disassembling and assembling. Elementary school students' initial reading and writing skills are the basic skills for subsequent reading and writing skills. Beginning reading and writing skills, especially lower classes such as classes I and II, require attention and strategies during the learning process in the form of methods or media. Puzzle media is one of the media that can help teachers in the process of learning initial reading skills. The formulation of the problem is: